Implantable and Semi-Implantable Hearing Aids: A Review of History, Indications, and Surgery - Bittencourt,Aline Gomes (2014)
Introduction  The complaints associated with the use of conventional amplifying hearing aids prompted research at several centers worldwide that ultimately led to the development of implantable devices for aural rehabilitation. Objectives  To review the history, indications, and surgical aspects of the implantable middle ear hearing devices. Data Synthesis  Implantable hearing aids, such as the Vibrant Soundbridge system (Med-El Corporation, Innsbruck, Austria), the Maxum system (Ototronix LLC, Houston, Texas, United States), the fourth-generation of Carina prosthesis (Otologics LLC, Boulder, Colorado, United States), and the Esteem device (Envoy Medical Corporation - Minnesota, United States), have their own peculiarities on candidacy and surgical procedure. Conclusion  Implantable hearing aids, which are currently in the early stages of development, will unquestionably be the major drivers of advancement in otologic practice in the 21st century, improving the quality of life of an increasingly aged population, which will consequently require increased levels of hearing support.